RADUAN NASSAR'S ARCHAEAL CLEARANCE: A POSSIBILITY FOR READING THE CONTEMPORARY WORLD - Pires Franco, Sandra Aparecida; Guizelim Simoes Girotto, Cyntia Graziella [UNESP]; Silva Mariano, Maria Luzia (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2018)
The objective of this text is to analyze the work of Archaic Lavoura, (1989) by Raduan Nassar as a possibility for a new reading of the contemporary world. The world reading comes from the way the author interprets and lives the social reality in which it is inserted. The work Lavoura Arcaica is a literary text of postmodern production of Brazilian literature, at which time it was reflected on the end of dominant ideologies and loss of references, denouncing the existential crisis of the subject. In this way, the present work refers to a documentary research, that approaches the analysis of the literary work exposing its structure and its social context. The theoretical assumptions are based on historical and dialectical materialism. The analysis of the literary work made it possible to understand that the author has the possibility of recreating reality through aesthetic reflection, leading the reader to appropriate knowledge of different times and spaces.
Keywords: Reading possibilities; World reading; Literary text